The Assessment of Pain and the Quality of Postoperative Pain Management in Surgical Patients - Tamer, Laika Kose; Dag, Gulten Sucu (Sage Publications Inc, 2020)
The aim of the study was to investigate surgical patients' pain experience and the quality of nursing care in managing acute postoperative pain. A descriptive cross-sectional study using a Strategic and Clinical Quality Indicators in Postoperative Pain Management Questionnaire collected data of 247 patients who underwent surgery in the surgical clinics of a state hospital. Data of 141 patients were included in the analysis. The mean scores for the scale items indicated that the quality of care was acceptable or low. The level of postoperative care, nursing interventions, and environmental subscales of the questionnaire were at an acceptable level, but pain management subscales of the questionnaire were low. These results suggest that health care, including measurable, applicable quality indicators, should be planned and evaluated to maintain professional nursing services, to achieve postoperative pain management and to relieve pain.
Keywords: pain; postoperative; pain management; quality of health care; nursing